Concepção histórica da incapacidade das mulheres na América Portuguesa: requerimentos das viúvas à Coroa no Século XVIII - Castro, Ana Luiza Barroso Caracas de (2021)
Contrary to the "myth" of the submissive and completely male-dominated woman, long rooted in historiography, it is clear that women, in the practice in force in Portuguese American society in the 18th century, had active participation in several sectors, not only family members and those with domestic influences, as well as in the economy, politics, management of large tracts of land and slaves, as well as participation in small businesses, depending on the occupied social status, from the granting of titles and privileges that they came to discriminate against the people who made up the colonial society. Despite this, based on the interpretations of the sources that made up the Common Law, more specifically the norms arising from the monarchy, applied from their own rules and intrinsically linked to local culture, women had their capacity to act and their behavioral freedom strictly limited by legal norms, especially those related to moral theology, which, despite having a relationship with ecclesiastical precepts, were concerned with issues related to restrictions on the autonomy of personal wills, which resulted in an even greater disparity between genders. Women had their capacity legally limited, in view of several moral and legal regulations that limited their performance, integrating the group of people in a "state" of vulnerability, thus acquiring the possibility of claiming benefits to be granted by the Portuguese Crown, arriving to conquer, in a paradoxical way, vast powers of command before that local community. The general objective of this research is to analyze the legal incapacity of women during the eighteenth century in Portuguese America, using as a basis not only the legislation that determined this condition in that period, as well as the historiographical records and works that explain themes involving the theme discussed here, but , mainly, the requests that were made by many women to the Portuguese Crown. The first was investigated by screening documents cataloged by the Research Project in the History of Law, funded by the Coordination for the Improvement of Higher Education Personnel (CAPES), called the Nucleus for Studies on Law in Portuguese America (NEDAP). chosen the letters compiled in the Digital Hemeroteca of the National Library, kept in the collection of “Documentos Históricos: Provedoria da Fazenda Real de Santos (RJ)” which, for the purposes of this research, brought more aspects of what were the requirements that characterized the consideration of women's incapacity within that society and, on the other hand, their legitimacy to plead certain questions of civil life before the Portuguese Crown, thus demonstrating , what is the personality assumed by women, more specifically widows, within eighteenth-century society. The second database, which also contributed to the results achieved in this dissertation, were the requests made by widows addressed to the Conselho Ultramarino, seeking a provision from the Portuguese Crown. The documents were accessed from the Projeto Resgate's virtual base, with a link referring to the captaincy of "Ceará (1618-1932)". A total of 696 (six hundred and ninety-six) documents were verified within the time frame of the year 1700 to the year 1800, with the aim of centralizing the studies in the 18th century; of these documents, only 14 (fourteen) applications were proposed by women, 5 (five) of them from widowed women, commonly claiming for the declaration of capacity to exercise civil life acts and management positions, raising their rights based on the social position occupied. It was concluded, from the requirements proposed by the widows and studied in this dissertation work, it was possible to understand that there was no exhaustive list of requirements to determine the ability of women to act in the most diverse spheres of society. all cited social status, including the title held by their late husbands and the influential relationships they managed to maintain close by. It was also possible to see, in relation to the applicants for validation of land grants, that these women already exercised power over the lands even before the request for declaration filed with the Crown, even maintaining a relationship of exchange of services to the the local administration and the provision of charges as a result of the fruits obtained in their patrimony, which demonstrates the performance of these widows in positions of power and social prestige. Despite this, there is no need to discredit the idea that there were many limitations suffered by these women, with a constant struggle of this gender for a more active participation in society, often submitting to male protection to facilitate greater acceptance and guarantee of quality of life within that context.